A VIRTUAL Sleep Apnoea management pathway For the work-up of Atrial fibrillation patients in a digital Remote Infrastructure: VIRTUAL-SAFARI. Issue 4 (31st October 2021) - Verhaert, Dominique V M; Betz, Konstanze; Gawałko, Monika; Hermans, Astrid N L; Pluymaekers, Nikki A H A; van der Velden, Rachel M J; Philippens, Suzanne; Vorstermans, Bianca; Simons, Sami O; den Uijl, Dennis W; Chaldoupi, Sevasti-Maria; Luermans, Justin G L M; et al.
Abstract: Aims: In atrial fibrillation (AF) patients, untreated sleep-disordered breathing (SDB) is associated with lower success rates of rhythm control strategies and as such structured SDB testing is recommended. Herein, we describe the implementation of a virtual SDB management pathway in an AF outpatient clinic and examine the utility and feasibility of this new approach. Methods and results: Prospectively, consecutive AF patients accepted for AF catheter ablation procedures without previous diagnosis of SDB were digitally referred to a virtual SDB management pathway and instructed to use WatchPAT-ONE (ITAMAR) for one night. Results were automatically transferred to a virtual sleep laboratory, upon which a teleconsultation with a sleep physician was planned. Patient experience was measured using surveys. SDB testing was performed in 119 consecutive patients scheduled for AF catheter ablation procedures. The median time from digital referral to finalization of the sleep study report was 18 [11–24] days. In total, 65 patients (55%) were diagnosed with moderate-to-severe SDB. Patients with SDB were prescribed more cardiovascular drugs and had higher body mass indices (BMI, 29 ± 3.3 vs. 27 ± 4.4kg/m 2, P  < 0.01). Patients agreed that WatchPAT-ONE was easy to use (91%) and recommended future use of this virtual pathway in AF outpatient clinics (86%). Based on this remote SDB testing, SDB treatment was recommended in the majority of patients. Conclusion: This novel virtual AF management pathway allowed remote SDB testing in AF outpatient clinics with a short time to diagnosis and high patient satisfaction. Structured SDB testing results in a high detection of previously unknown SDB in AF patients scheduled for AF ablation.